The Development Potential of Lombang-Lombang Beach Tourism in Increasing Community Income - Dahlan, Risda; Heryati, Yati; Arsyad, Muhammad (Golden Ratio of Social Science and Education, 2024)
Indonesia is a country rich in natural beauty, diverse flora and fauna, and a wide range of cultures, all of which have the potential to generate substantial foreign exchange through tourism. In general, tourism is seen as a sector that can drive economic growth by increasing both community income and local revenue when managed and developed optimally. Lombang-Lombang Beach is one such natural attraction that is frequently visited by both locals and tourists, especially during holidays and regular days. The purpose of this research is to explore the efforts made by the local community to develop Lombang-Lombang Beach as a tourist destination and how it contributes to increasing community income. This study uses qualitative methods, with data sourced from both primary and secondary sources. Data collection techniques include observation, interviews, and documentation. The collected data will then be processed through data reduction, data presentation, and finally, drawing conclusions.